Psychological Factors Linking With Digestion W.S.R To Charaka Samhita - Shukla, Megha; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
“Rasavahini Dushyanti Chintyanam Cha Atichintanaat” Ch.Vi. 5/13 This verse directly indicating that psychological factors like Ati-Chinta or excessive stress affect Rasavahini. Hṛdaya (heart) and Dasha Dhamani (arteries) have been considered as Moolasthān (origin) of Rasavaha Srotas. Hṛidaya is organ heart which is situated in the middle mediastenum of thorax and pumps the blood along with Rasa Dhātu (Plasma) throughout the body continuously. Hṛdaya works as storage and pumping action of Rasa Dhātu, after that Daśa Dhamanīes transports that Rasa Dhātu which is pure minutest essence of properly digested food through all corners of body. In Ayurveda; Charaka samhita states at various places that Jatharagni can be affect by many of psychological factors like Chinta (Anxiety), Shoka (grief), Bhaya (fear), Krodha (anger), Dukha (sorrow), Ahridya ashan gandha (unpleasant food, smell and sights) etc. They also very well known about the relation of mana with digestion. They also told about the brain-gut connection with various psychosomatic disorders like Amavat (rheumatoid arthritis), Unmad (mental disorders), Atatvaabhinivesha (Obsessive compulsive disorder) , Apsmar ( Epilepsy), Ajirna (Indigestion), Hridya roga ( heart disease) .